Pemberdayaan Mahasiswa melalui Rancang Media Interaktif Guna Meningkatkan Efektivitas Promosi Kesehatan Masyarakat - Adi Tri Atmaja; Okta Mela Cikal Santoso; Rafiqa Ilma Meinina; Fufa Masruro; Risa Yanuarti Sholihah; Rista Dwi Ani; Siti Muarifah (Universitas Pahlawan Tuanku Tambusai, 2026)
Health promotion is often hampered by the phenomenon of digital fatigue and the gap in pedagogical competence of health students in reducing complex medical terminology into lay language. This community service aims to empower health students through the reactualization of interactive analog displays as an alternative instrument for inclusive community education. Adopting the participatory action learning method, it was constructed in four stages: dissemination, workshops, clinical simulations, and implementation in three secondary education institutions in Blitar City. The intervention results indicated a comprehensive escalation in the cognitive and psychomotor domains of participants, as evidenced by the successful engineering of infrastructure-friendly dynamic manual display instruments, fabrication cost efficiency and mobilization portability. Clinical understanding skills with basic instructional design principles through interactive analog media have proven to be able to bridge the epistemological disparity between health workers and the community and produce health cadres who are resilient, communicative, and adaptive to infrastructure.